Kajian Konsep Arsitektur Fungsionalisme pada Bangunan Kantor Sewa - Naufal, Muhammad Amin; Anisa, Anisa (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the application of the functionalism architectural concept in rental office buildings in Jakarta. The research employs a qualitative approach with case studies on three buildings: Midplaza Office Building, Menara Cakrawala, and The Plaza Office Tower. The study focuses on the principles of functionalism, including